VERBA DERIVASIONAL DALAM BAHASA SUMBAWA DIALEK SUMBAWA BESAR - , Rahmad Hidayat ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study describes the derivation process becomes a verb in the scope of affixation and conversion in Sumbawa language Sumbawa Besar dialect. Thus, the derivational verb has formed. Derivational verbs in this scope are formed by attaching affixes to the base form of the word-class nouns, adjectives, verbs, pronouns, numeral, and adverbs. In the meantime, this research also describes the various types of semantic units and semantic features which contained by derivational verbs as a result of the derivation process. The goal is to be able to see changes in the behavior of verbs both at the level of morphology, syntactic, and semantics. This study adhere the indicator of lexical identity changes as a tool to determine a process which is said to be a derivational process. Such change of identity was traced by using three ways: (1) changes the word class, (2) if the class of the word does not change,, change the meaning and features of meaning and grammatical subclasses changes are defined, and (3) testing in the syntactic construction in order to see changes in behavior verbs. The data of the research is provided by using observation method which refer to the record techniques and introspective method. As an effort to validate the data, the researcher uses interview methods with inducement techniques as a basic technique to the informant. This is done in order to make the available data actually recognized its use by speakers. Furthermore, the method of analyzing data uses lexical identity changes testing as above. Finally, the presentation of the results of analyzing the data uses formal methods and informal methods. The results obtained as described in the formulation of research problems namely (1) all the affixes which formed verb are entirely prefix, they are